Review of Euthycerina Malloch (Diptera, Sciomyzidae), with description of a new species from Chile - Mortelmans, Jonas; Hendrix, Jef (Zootaxa, 2020)
We review and summarize the present knowledge of the Neotropical genus Euthycerina Malloch, 1933. Habitus and male terminalia are described and figured in detail for the first time. Euthycerina uachi sp. nov. is described, based on two males and four females from two locations in the province of Valdivia, Chile. An illustrated key is given for the three described species of Euthycerina, together with maps, phenology plots, and a summary of diagnostic characters that will enable researchers to confidently identify all species of Euthycerina.